The effect of thursday night games on in-game injury rates in the national football league - Perez, J.; Burke, J.; Zalikha, A. K.; Damodar, D.; Geller, J. S.; Buskard, A. N. L.; Kaplan, L. D.; Baraga, M. G. (The American Journal of Sports Medicine, 2020)
Background: Although claims of increased injury rates with Thursday night National Football League (NFL) games exist, a paucity of data exist substantiating these claims.